THE ROLE OF LOVE OF MONEY AND RELIGIOSITY IN MACHIAVELLIAN RELATIONS WITH THE ETHICAL PERCEPTION OF UMKM IN THE CULINARY SECTOR IN MAKASSAR CITY: THE ROLE OF LOVE OF MONEY AND RELIGIOSITY IN MACHIAVELLIAN RELATIONS WITH THE ETHICAL PERCEPTION OF UMKM IN THE CULINARY SECTOR IN MAKASSAR CITY - Muhammad Anis, Harry; Raprayogha, Rusdi; Bakhtiar, fauzia (Study of Scientific and Behavioral Management, 2023)
This research is a type of research with a quantitative approach with a sample of 150 respondents at MSME players in Makassar City with a sample withdrawal using the Hair formula. With data processing using SmartPLS.This application is also used to test or find out how the Machiavellian, Love of Money, and Religiosity variables relate to the Ethical Perceptions of MSMEs in the Makassar City Culinary Sector. The results of this study indicate that: 1. Machiavellian has a negative and significant effect on the ethical perceptions of MSMEs in the culinary sector in Makassar City; 2. Machiavellian has a positive and significant effect on the love of money of MSMEs in the culinary sector in Makassar City; 3. Love of money has a negative and significant effect on the ethical perceptions of MSMEs in the culinary sector in Makassar City; 4. Love of Money mediates the influence of Machiavellian on the Ethical Perceptions of MSMEs in the Culinary Sector in Makassar City; 5. Religiosity moderates the influence of Machiavellian on the Ethical Perceptions of MSMEs in the Culinary Sector in Makassar City. Keywords: Machiavellian, Love of Money, Religiousness, Ethical Perceptions of MSMEs.